Determining a subsidy rate for Taiwan's recycling glass industry: an application of bi-level programming - Shih, H-S; Cheng, C-B; Wen, U-P; Huang, Y-C; Peng, M-Y (The Journal of the Operational Research Society, 2012)
This study attempts to optimize the operations of the Recycling Fund Management Board (RFMB), founded by the Environmental Protection Administration of the R.O.C. Government (on Taiwan), through the decision of a subsidy rate for the domestic glass recycling industry. The hierarchical and interactive nature between the two parties is modelled by bi-level programming, where the RFMB plays the upper-level decision unit while the recycling industry is the lower-level counterpart. In order to solve the problem by optimization software, the bi-level formulation is transformed to a single-level problem via Karush-Kuhn-Tucker optimality conditions and is further transformed to a 0−1 mixed integer programming problem by variable substitution. The problem is solved with real-world data, and the obtained solutions are analysed and compared with the RFMB's current operations. The results suggest that the proposed approach can improve the operations of the RFMB.